Aegle Marmelos Enhances Gastric Mucosal Protection: Relevance for NSAIDS-Induced Gastric Mucosal Injury - P.Singh; D.Guha (Al Ameen Medical College, 2012)
Objective: In order to study the gastroprotective effect of Aegle marmelos extract (AM), this study was undertaken on aspirin-induced ulcerogenesis in cannulated free-moving rats. Background: Most of the non-steroidal anti-inflammatory drugs (NSAIDs) including aspirin (ASP) cause gastric ulcer. The efficacy of several plants for the treatment of gastroduodenal disease is confirmed by clinical research, while basic scientific research helps us to uncover the mechanisms by which these plants exert their therapeutic effects. Method: To assess the possible antiulcer effect of AM, lesion index, gastric secretions glycoprotein levels and mucosal histopathology were determined in ASP induced gastric mucosal injury in cannulated free-moving rats. Results: Pretreatment with AM significantly prevented the development of gastric mucosal lesion and decreased the gastric toxicity produced by ulcerogen. In addition, ulcerated rats showed depletion of gastric wall mucus, glycoproteins and enhanced gastric acid secretion whereas treatment with AM prevented these ASP induced responses in cannulated free-moving rats. Histological studies confirmed the results. Conclusion: The present finding suggests that AM promotes ulcer protection by the decrease in ulcer index, gastric secretions and increase in the glycoprotein level, gastric mucin content and maintenance of mucosal epithelium. AM protects the gastric mucosa against ulceration by its antisecretory and cytoprotective property.